Cracking susceptibility of full-sibs of a cross of a cracking tolerant and cracking susceptible sweet cherry: Relation to cuticle characteristics, microcracking and calcium - Moritz Knoche; Loise Grosset-Grange; José Quero-García; David Alletru; Lina Boutaleb (PLoS ONE, 2025)
Rain cracking compromises quality and quantity of sweet cherries worldwide. Cracking susceptibility differs among genotypes. The objective was to (1) phenotype the progeny of a cross between a tolerant and a susceptible sweet cherry cultivar for cuticle mass per unit area, strain release on cuticle isolation, cuticular microcracking and calcium/dry mass ratio and (2) relate these characteristics to cracking susceptibilities evaluated in laboratory immersion assays and published multiyear field observations. Mass of the dewaxed cuticle per unit area and strain release upon cuticle isolation were significantly related to cracking susceptibility in lab or field. Cuticular microcracking in the stylar end region as indexed by infiltration with acridine orange was more severe in susceptible than in tolerant genotypes and significantly correlated with susceptibility to cracking in lab and field. The Ca/dry mass ratio was lower (-8%) for susceptible than for tolerant genotypes. Fruit that cracked early had less Ca than those that cracked later. Only the Ca/dry mass ratio of the stylar end region was significantly correlated with cracking susceptibility in the field. Based on stepwise regression analyses microcracking of the cuticle accounted for most of the cracking susceptibilities in field and lab (partial r2 = 0.331 to 0.338 for field vs. r2 = 0.326 to 0.453 for lab). The variability in cracking susceptibility accounted for increased to a r2 = 0.571 (lab) when adding mass of dewaxed cuticle, up to r2 = 0.421 (field) when adding the Ca/dry mass ratio in the stylar end region or up to r2 = 0.478 (field) when entering the strain release on isolation into the model. A protocol for phenotyping is suggested that allows larger progenies to be phenotyped for microcracking, DCM mass and strain release.